Effect of transverse and longitudinal reinforcement ratios on the behaviour of RC T-beams shear-strengthened with embedded FRP BARS. (15th April 2021) - Sogut, Kagan; Dirar, Samir; Theofanous, Marios; Faramarzi, Asaad; Nayak, Amar Nath
Abstract: Seven reinforced concrete (RC) T-beams, comprising two unstrengthened (control) beams and five beams strengthened in shear with embedded FRP bars, were tested to failure. The test parameters were steel-to-FRP shear reinforcement ratio and tension reinforcement ratio. A nonlinear finite element (FE) model was developed, validated and used to conduct parametric studies. The experimental and FE results showed that the concrete and FRP contributions to shear resistance as well as the total shear force capacity all decrease with increasing steel-to-FRP shear reinforcement ratio. The tension reinforcement ratio influenced the failure mode of the tested and modelled beams but had insignificant impact on shear strength enhancement. The experimental results were compared with the FE and Concrete Society Technical Report 55 predictions. The FE model correctly reproduced the experimental results and gave accurate predictions, with a mean predicted-to-experimental ratio of 1.04, whereas TR55 gave conservative predictions, with a mean predicted-to-experimental ratio of 0.42.